2010
DOI: 10.1136/bmj.c1964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accelerated rehabilitation on function after ankle sprain: randomised controlled trial

Abstract: Objective To compare an accelerated intervention incorporating early therapeutic exercise after acute ankle sprains with a standard protection, rest, ice, compression, and elevation intervention. Design Randomised controlled trial with blinded outcome assessor. Setting Accident and emergency department and university based sports injury clinic. Participants 101 patients with an acute grade 1 or 2 ankle sprain. Interventions Participants were randomised to an accelerated intervention with early therapeutic exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 46 publications
(43 reference statements)
1
127
0
5
Order By: Relevance
“…There is also an abundance of literature investigating injury epidemiology in field based sports (98 of the studies included in our analysis were field-based focused). The high risk of ankle sprain has promoted an appropriate research response, as a large number of methodologically rigorous randomised control trials now exist investigating the effect of different interventions in injury rehabilitation (54,(228)(229)(230)(231) and prevention (232)(233)(234).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an abundance of literature investigating injury epidemiology in field based sports (98 of the studies included in our analysis were field-based focused). The high risk of ankle sprain has promoted an appropriate research response, as a large number of methodologically rigorous randomised control trials now exist investigating the effect of different interventions in injury rehabilitation (54,(228)(229)(230)(231) and prevention (232)(233)(234).…”
Section: Discussionmentioning
confidence: 99%
“…This functional treatment has been shown to speed recovery when compared with immobilization. Bleakley et al 38 …”
Section: Management Of Lateral Ankle Sprainsmentioning
confidence: 99%
“…Because of these reasons, rehabilitation of athletes is initiated as quickly as possible, while respecting the constraints of healing [9]. In their study, Bleakley et al showed that exercise during the first week after sustaining an ankle sprain improved ankle function, which supports early rehabilitation [10].…”
Section: Introductionmentioning
confidence: 81%